2018
DOI: 10.1080/1028415x.2018.1501533
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid triggers inflammatory responses in N42 cultured hypothalamic cells partially via ceramide synthesis but not via TLR4

Abstract: A high-fat diet induces hypothalamic inflammation in rodents which, in turn, contributes to the development of obesity by eliciting both insulin and leptin resistance. However, the mechanism by which long-chain saturated fatty acids trigger inflammation is still contentious. To elucidate this mechanism, the effect of fatty acids on the expression of the pro-inflammatory cytokines IL-6 and TNFα was investigated in the mHypoE-N42 hypothalamic cell line (N42). N42 cells were treated with lauric acid (LA) and palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 73 publications
5
50
0
Order By: Relevance
“…However, when ceramide synthesis was blocked using l-cycloserine, PA-induced inflammation was also blocked. In agreement with our model, Sergi et al 70 also provided evidence showing that an unsaturated fatty acid co-treatment was able to block PAinduced inflammation in the mHypoE-N42 hypothalamic cell line.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, when ceramide synthesis was blocked using l-cycloserine, PA-induced inflammation was also blocked. In agreement with our model, Sergi et al 70 also provided evidence showing that an unsaturated fatty acid co-treatment was able to block PAinduced inflammation in the mHypoE-N42 hypothalamic cell line.…”
Section: Discussionsupporting
confidence: 91%
“…Sergi et al 70 also provided supporting evidence to the present study by demonstrating that PA does not directly activate the TLR4 inflammatory response in vitro. When CLI-095 was used (an established blocker of downstream signaling events mediated by TLR4), it was found that PA still led to increased pro-inflammatory cytokine expression.…”
Section: Discussionsupporting
confidence: 86%
“…The saturated long-chain fatty acid palmitic acid (PA) is a major circulating saturated fatty acid, and the plasma concentration of PA is significantly increased in obesity subjects [23,24]. PA was often used as a high fat inducer in vitro, we analyzed whether common ingredients of SIF -daidzein and genistein-could improve the oxidative stress induced by PA. We found that cell viability of N42 cells, which is an embryonic mouse hypothalamic cell line [25], was suppressed by PA, while significantly increased cell viability was detected by CCK-8 assay in N42 cells exposed to PA/daidzein or PA/genistein combined treatment ( Figure 5A). Moreover, we found significantly increased reactive oxygen species (ROS) accumulation in N42 cells after PA treatment by fluorescent dihydroethidium (Eth) labeling, while ROS accumulation was decreased after daidzein or genistein treatment ( Figure 5B, 5C).…”
Section: Soy Isoflavones Could Improve Palmitic Acid-induced Apoptosimentioning
confidence: 98%
“…Recent studies have shown that ceramide effects in the hypothalamus contribute to leptin resistance. It has been shown that palmitate, a lipid long known to cross the blood-brain barrier ( 180 ) and also induce inflammation ( 181 ) does so in the hypothalamus partially through ceramide synthesis ( 182 ). Mice subjected to intravenous emulsions of saturated fatty acids had ceramides accumulate in the hypothalamus, indicating a hypothalamic role for ceramide detection and regulation ( 108 ).…”
Section: Leptin and Ceramidesmentioning
confidence: 99%